Carving motifs in timber houses of Kelantan and Terengganu: sustaining Malay architecture identity - Kamaruddin, Zumahiran; Said, Ismail (2010)
This paper presents an analytical study on the visual forms of motifs of carved components in the houses of Kelantan and Terengganu. Thirteen sets of measured drawings of the components from nine houses in Kelantan and four houses in Terengganu were analyzed. The drawings were obtained from Centre for the Study of Built Environment in the Malay World at the Universiti Teknologi Malaysia. Data from the drawings and feedbacks from two woodcarvers revealed that there were four types of carved components: ventilation panels of wall, door and window, railings, gate panel and stringers. The motifs were flora, geometry, Arabic calligraphy and cosmic features depicted in two and three dimensional compositions either in relief or non-relief forms. Consistency in patterns of motif, particularly flora motifs, results to an establishment of identity to the vernacular architecture of north-eastern region of Peninsular Malaysia. The components were crafted in relation to the house form and architectural elements such as wall, door, window, stair and gate. The significant aspect of the placement of the carvings in the houses is that it enhances the aesthetic of the houses and signifies the architectural identity of the north-eastern states. To sustain the woodcarving as Malay architecture heritage, this paper presents a framework for the existing craftsmen to continue making carved components for urban housing markets. The suggested components are ventilation panels of door, window and wall, door leaves and window railings